Timing, investment opportunities, managerial discretion, and the security issue decision - Jung, Kooyul; Kim, Yong-Cheol; Stulz, RenéM. (Journal of Financial Economics, 1996)
This paper investigates the ability of the pecking-order model, the agency model, and the timing model to explain firms' decisions whether to issue debt or equity, the shock price reaction to their decisions and their actions afterward. We find strong support for the agency model. Firms often depart from the pecking order because of agency considerations. We fail to find support for the timing model.